The Main Success Factors of Smart Branding: A Systematic Literature Review - Sabilaturrizqi, Mashudah; Susanto, Tony Dwi (Institut Teknologi Bisnis AAS Indonesia, 2024)
Many countries around the world have now adopted smart branding. However, the implementation of smart branding in some cities still has obstacles or challenges. This paper aims to contribute to formulating a conceptual model for smart branding. A literature review from 2017 to 2024 used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method to examine the term smart branding. From the literature review, ten dominant factors influence the success of smart branding, namely government support, creativity and innovation, the power of social media, stakeholders involvement, city residents, culture, economic development, technology advances, tourism development goals, and efficient public transport. These findings enrich the theoretical exploration of smart branding.